Surgical treatment of renal cancer. Tumor thrombus within local veins as surgical problem - Borówka, Andrzej; Dobruch, Jakub (Contemporary Oncology/Współczesna Onkologia, 2005)
Renal cell carcinoma (RCC) is most prominent among all kidney cancers. Its incidence significantly rose during recent years. Wide spread use of imaging techniques especially transabdominal ultrasound has led to increase in incidental renal tumors diagnosis including cancers and dominating among them renal cell carcinoma. Penetration within renal vein and then within inferior vena cava is one way of this cancer growth. The presence of vein thrombus which is diagnosed in 4-10% of patients operated on renal cancer is not per se unfourable prognostic factor. That is why patients with localized disease and diagnosed vein thrombus should be operated independently on its extension into subhepatic part of vena cava or into right atrium, however under condition that surgery brings improve of patients prognosis. Excision of tumor thrombus within subphrenic part of vena cava is not significantly troublesome but involvement of supraphrenic parts or right atrium necessitates cooperation with cardio or thoracosurgeons. Survival of patients operated on renal cell carcinoma with extension within veins depends mostly on stage and grade of primary tumor.